Ferroptosis Is a Potential Novel Diagnostic and Therapeutic Target for Patients With Cardiomyopathy - Zhai, Zhenyu; Zou, Pengtao; Liu, Fuxiang; Xia, Zirong; Li, Juxiang (Frontiers in Cell and Developmental Biology, 2021)
Cardiomyocyte death is a fundamental progress in cardiomyopathy. However, the mechanism of triggering the death of myocardial cells remains unclear. Ferroptosis, which is the nonapoptotic, iron-dependent, and peroxidation-driven programmed cell death pathway that is abundant and readily-accessible, was not discovered until recently with a pharmacological approach. New researches have demonstrated the close relationship between ferroptosis and the development of many cardiovascular diseases, and several ferroptosis inhibitors, iron chelators, and small antioxidant molecules can relieve myocardial injury by blocking the ferroptosis pathways. Notably, ferroptosis is gradually being considered as an important cell death mechanism in the animal models with multiple cardiomyopathies. In this review, we will discuss the mechanism of ferroptosis and the important role of ferroptosis in cardiomyopathy with a special emphasis on the value of ferroptosis as a potential novel diagnostic and therapeutic target for patients suffering from cardiomyopathy in the future.